Evaluating the effectiveness of drug and therapeutics committees (DTCs) in controlling irrational drug use: A retrospective analysis - Yang, Jing; Zheng, Lei; Guan, Yu‐yao; Li, Pi‐bao; Lv, Yong‐tao (Journal of clinical pharmacy and therapeutics, 2022)
What Is Known and Objective This study aimed to explore methods to optimize the function of Drug and Therapeutics Committees (DTCs) in controlling irrational drug use. Clinical pharmacologists contribute their specific knowledge and skills to DTCs and help guide rational therapeutics. The DTC is the highest organization of hospital pharmacy management. Methods From January 2016 to August 2021, the DTC promoted the optimization of clinical drug treatment schemes and reduced unreasonable drug use by improving the organizational framework, clarifying the division of functions, regularly monitoring drug use, organizing expert comments, scientific decision‐making and functional intervention. During this time, we statistically analysed typical management cases, irrational drug use and drug cost to evaluate the effectiveness of the DTC’s management. Results and Discussion The DTC’s intervention led to a significant reduction in prescribing errors (65.98%, p < 0.05); the intervention acceptance rate increased by 16.37%; and the rate of problem resolution increased by 45.84% (p < 0.05). The level of drug treatment was improved, and the proportion of patients’ drug expenses was reduced. What Is New and Conclusion The DTC carried out a series of continuous improvement work that played a significant normative role in clinical drug use. Giving more power to the DTCs can significantly improve the level of drug treatment and reduce unreasonable drug use, which reduces unnecessary drug expenses. There are six working groups under the DTC, which are responsible for the specific daily work and reporting of the work at the pharmaceutical meeting every quarter. The specific functions of the DTC are more effectively implemented by this division of labor. Among them, the key monitoring drug management group, prescription review management group, and the rational drug use service group are responsible for monitoring rational drug use.